2009
DOI: 10.1093/humrep/dep411
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of subtle and severe menstrual disturbances in exercising women: confirmation using daily hormone measures

Abstract: This study suggests that approximately half of exercising women experience subtle menstrual disturbances, i.e. LPD and anovulation, and that one third of exercising women may be amenorrheic. Estimates of the prevalence of subtle menstrual disturbances in exercising women determined by the presence or absence of short or long cycles does not identify these disturbances. In light of known clinical consequences of menstrual disturbances, these findings underscore the lack of reliability of normal menstrual interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(195 citation statements)
references
References 34 publications
6
178
1
5
Order By: Relevance
“…Menstrual disturbances in highly active women have been suggested to reflect oestrogen deficiency due to low body weight, weight loss, or excessive exercise (25)(26)(27)45,46). In the current study, adjustment for BMI did not significantly alter the observed relationships between LTPA and menstrual cycle characteristics.…”
Section: Discussioncontrasting
confidence: 45%
“…Menstrual disturbances in highly active women have been suggested to reflect oestrogen deficiency due to low body weight, weight loss, or excessive exercise (25)(26)(27)45,46). In the current study, adjustment for BMI did not significantly alter the observed relationships between LTPA and menstrual cycle characteristics.…”
Section: Discussioncontrasting
confidence: 45%
“…Self-reported current menstrual status was then confirmed prospectively by classifying menstrual cycles by length of the intermenstrual interval, the presence of menses, and characteristic reproductive hormone profiles [16]. These determinations were made from the measurement of daily urinary ovarian steroid metabolites, estrone-1-glucuronide (E1G) and pregnanediol glucuronide (PdG), as previously described [16,38].…”
Section: Current Menstrual Status Categorizationmentioning
confidence: 99%
“…These determinations were made from the measurement of daily urinary ovarian steroid metabolites, estrone-1-glucuronide (E1G) and pregnanediol glucuronide (PdG), as previously described [16,38]. E1G and PdG were measured in each urine sample using microtiter plate competitive enzyme immunoassays and a polyclonal capture antibody supplied by Coralie Munro University of California (Davis, CA) as previously reported [12,16].…”
Section: Current Menstrual Status Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…From delaying the onset of menarche 27 to causing subclinical menstrual disorders, oligomenorrhea, and amenorrhea, 28 exercise can impact menstrual function in several ways. Oligomenorrhea is defined as menstrual cycles occurring at intervals longer than 35 days, and secondary amenorrhea is defined as the absence of menstrual cycles for more than 3 months in a previously menstruating individual.…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%